GOVERNANCE IMPACTS OF NATIONAL PARK POLICIES ON TRADITIONAL SETTLEMENT DEVELOPMENT: A CASE STUDY OF QIONGLIN VILLAGE, KINMEN, TAIWAN - Yu-Ting Hung; Kan-Chung Huang; Yao-Lin Chang (International Journal of Application on Economics and Business, 2026)
Traditional settlements located within national parks operate under highly regulated governance regimes that shape local development trajectories. While national park policies are designed to protect cultural landscapes and environmental assets, they also reconfigure institutional incentives, spatial practices, and stakeholder behavior, with significant implications for local development outcomes. Grounded in governance-oriented perspectives, this study conceptualizes national park policies as dynamic governance arrangements integrating regulatory instruments, institutional incentives, and stakeholder interactions. Using a qualitative case study of Qionglin Village in Kinmen National Park, Taiwan, the study draws on semi-structured interviews with local residents, academic experts, and tourism practitioners. Data were analyzed using thematic analysis, with attention to coding consistency and cross-stakeholder triangulation to enhance analytical rigor. The findings reveal that governance impacts emerge through the interaction of regulatory constraints, institutional incentives, and local responses. While strict land-use and architectural controls initially generated resistance, they gradually gained legitimacy as their long-term conservation benefits became evident. Nevertheless, persistent constraints remain, particularly in infrastructure provision, spatial flexibility, and tourism-related economic opportunities. Transferable development rights function as a key mediating governance mechanism, partially offsetting regulatory restrictions while facilitating adaptive development strategies. The study advances governance theory by demonstrating that regulatory legitimacy in protected areas is dynamically co-produced through iterative interactions between institutional design and local agency. The findings also provide transferable insights for enhancing adaptive and context-sensitive governance and institutional effectiveness in inhabited protected areas.